Hospital pharmacy services in the Pacific Island countries. Issue 1 (15th July 2014) - Penm, Jonathan; Chaar, Betty; Moles, Rebekah
Abstract Rationale, aims and objectives Non‐communicable diseases have become an increasing problem in the Pacific Island countries (PICs). With the medical supply system often attached to hospitals in PICs, the training of hospital pharmacy staff has become increasingly important. This study aimed to explore hospital pharmacy services in the PICs using these validated surveys (BS26–27 and BS28–31 surveys) focusing upon hospital pharmacists' influence on prescribing and quality use of medicines. Method The BS26–27 and BS28–31 surveys were distributed online to pharmacy directors in hospitals in the PICs in 2011 and 2013, respectively. Surveys were made available in both English and French. Results In total, data from 55 hospitals were received (77% of the hospital sample in PICs) for either the BS26–27 or BS28–31 survey. From the responses received, 97% (36/37) of hospitals had a formulary, with 81% (26/32) of hospitals having a Pharmacy and Therapeutics (P&T) committee. Furthermore, 67% (24/36) of respondents stated that they provided some sort of clinical pharmacy service. On average, hospitals had two pharmacists involved in clinical pharmacy services. In BS28–31, over 75% (n = 27) of respondents believed having a strong relationship with other health care professionals, having effective communication skills and taking professional responsibility for the medicines prescribed as 'mostly' or 'strongly' facilitating clinical services. Conclusions Hospital pharmacists' participation on P&T committee and clinical services is common in the PICs. Such services enhance medication selection and reduce wastage. Although there are still too few hospital pharmacists in PICs, additional support aimed at enhancing their team building and communication skills will allow them to expand their roles and continue to improve patient health outcomes.